Deficiency in histone acetylation in nontransforming host range mutants of polyoma virus. - Schaffhausen, B S (1976)
Histones H3 and H4 derived from transforming wild-type polyoma and simian virus 40 particles show extensive acetylation compared to the histones of the host cells. The same histone fractions derived from nontransforming host range mutants of polyoma virus fail to show this high degree of acetylation.